OVERVIEW OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD): INDIVIDUALIZED TREATMENT BASED ON CLINICALLY ACTIONABLE PHENOTYPES (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on clinically meaningful COPD phenotypes and the treatable-traits approach, in order to clarify the value of personalized treatment in practice, especially in resource-limited settings.Methods: This was a focused narrative review. Key documents published or updated through November 2024, including the GOLD 2025 report, were purposively selected from PubMed, the Cochrane Library, Google Scholar, and the GOLD website using keywords related to COPD, phenotype, exacerbations, eosinophils, and treatable traits. Rather than aiming for exhaustive retrieval, the review prioritized foundational, practice-influencing sources directly relevant to treatment decisions.Results: The evidence consistently shows that COPD is a heterogeneous disease with several clinically relevant profiles, including the frequent exacerbator phenotype, patients with asthma-like features or type 2 inflammation, emphysema-predominant disease, chronic bronchitis-predominant disease, and comorbidity-dominant presentations. The GOLD A-B-E framework remains an appropriate starting point, while phenotype- and trait-based assessment helps refine indications for inhaled corticosteroids, exacerbation prevention strategies, management of hyperinflation, and control of major comorbidities.Conclusion: In stable COPD, phenotype-based assessment should be considered a complementary layer built upon the current GOLD framework to support personalized treatment.
Keywords: COPD; phenotype; individualized treatment; treatable traits; GOLD; eosinophils.